Survey of ICT and Education in Africa : Comoros Country Report - Ngombo, Florence; Isaacs, Shafika (World Bank, Washington, DC, 2012)
This short country report, a result of larger Information for Development Program (infoDev) - supported survey of the Information and Communication Technologies (ICT) in education in Africa, provides a general overview of current activities and issues related to ICT use in education in the country. Comoros - one of the poorest and smallest countries in the world, with a coup-prone, turbulent history over the past few decades - Comoros boasts a national ICT policy as an expression of its government's commitment to promote improved ICT infrastructure, as well as access and usage across the education system. There are, however, very few initiatives underway that promote the use of ICTs in Comoran schools and education institutions.